A Study the Role of Water and the Sustainable Development (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Water is a crucial natural resource that serves as a primary source of water for irrigation, drinking, and industrial use in India. Despite its importance, Water resources in India are rapidly depleting due to increasing demand, climate change, and unsustainable management practices. Sustainable development, which aims to harmonize economic growth, social inclusion, and environmental sustainability, is paramount in addressing these water challenges. In this context, it is crucial to revisit the Water laws in India to ensure sustainable resource management. The current legal framework for Water in India is fragmented, outdated, and ineffective. the significance of Water has grown. Currently, private-Water resources provide about 90% of the domestic and commercial water needs as well as around 65% of the irrigation needs. However, people frequently mistakenly believe that this valuable resource is boundless and unbounded. As a result, the general public frequently overlooks crucial Water issues such its scientific management, conservation, and augmentation.